The Correlation Between MIR-146A and Platelet to Lymphocyte Ratio to Liver Fibrotic on Hepatitis B - S.R, Brillian Van Fito; Budi S, R. Satriyo; Pramana, Triyanta Yuli (UI Scholars Hub, 2022)
Introduction. Liver fibrosis is a pathological condition as a recovery tissue respond, characterized by excessive extracellular matrix deposit. MicroRNA (miRNA or miR) has a pivotal role on progression of hepatic cirrhosis. Platelet to lymphocyte ratio (PLR) could be as a good predictor of liver fibrosis. This study aimed to find the correlation between miR-146a and PLR with liver fibrosis in Hepatitis B.Method. The cross sectional study conducted in Gastroenterohepatology Clinic of Internal Medicine Department RSUD Dr. Moewardi Surakarta in Januari – Juli 2020, involving 26 Hepatitis B naïve patients. Complete blood count, serum creatinine, liver enzyme, HBsAg, miR-146a, elastography measurement using FibroScan were performed.Results. The average age of patients was 49 (SD 11) years, mainly men (n : 17, 66%). The results from bivariate analysis demonstrated that miR-146a was significantly associated with liver fibrosis (r = 0,639 dan p < 0,001). PLR was also significantly associated with liver fibrosis (r = -0,455 dan p = 0,020). Conclusion. There was a significant correlation between miR-146a and PLR with liver fibrosis on Hepatitis B.